In vivo Anti-arthritic Activity of Soft Coral Lobophytum sp. From Southeast Sulawesi in Freund’s Complete Adjuvant Induced Arthritis - Fristiohady, Adryan; Nurpajriani, Nurpajriani; Malaka, Muhammad Hajrul; Ilyas Y, Muhammad; Pascayantri, Asniar; Haruna, Lidya Agriningsih; Purnama, La Ode Muh. Julian; Asasutjarit, Rathapon; Sahidin, Idin; Yodha, Agung Wibawa Mahatva (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2024)
Rheumatoid arthritis (RA) is a systemic, progressive, chronic autoimmune inflammatory disease that affects tissues, organs, and damages synovial joints. The RA can be treated with DMARD (disease modifying anti rheumatic drugs), such as methotrexate. However, the use of this drug long-term can cause side effects. Soft coral Lobophytum sp. has secondary metabolite compounds such as flavonoids, alkaloids, and terpenoids which has an anti-inflammatory activity, which beneficial for anti-rheumatoid arthritis agent. This study aims to determine the potential of anti RA in Lobophytum sp. using in vitro and in vivo. The anti-inflammatory assay for anti RA in vitro was performed by stabilization of human red blood cell (HRBC) membrane. In addition, anti RA was performed in arthritis model mice by induction of complete Freund’s adjuvant (CFA) by administering LEA once daily orally for 15 days. It was found that the ethyl acetate of Lobophytum sp. (LEA) reduced the haemolysis and increased the stability of HRBC membrane. Furthermore, LEA also showed anti RA by decreasing the edema in mouse paw at dose of 50 mg.kg-1 BW (LEA50), 100 mg.kg-1 BW (LEA100), and 200 mg.kg-1 BW (LEA200), respectively with 2.5 mg.kg-1 BW of methotrexate as positive control (C+) with P<0.05. Moreover, LEA200 demonstrated highest efficacy and showed no significant different with C+ (P>0.05). In conclusion, our research has shown that LEA has anti-inflammatory for treatment of rheumatoid arthritis from in vitro and in vivo studies.